ANCAMAN BENCANA DAN KEBIJAKAN PENANGANANNYA DI DAERAH - Ferry Firdaus, Rustan A. dan (Jurnal Borneo Administrator, 2011)
This article is set to explore the important role at Indonesian local government which have been mandated by the constitution to manage disasters in their respective regions. It also encourages that sustainable disaster management be included in the local governments development plan documents, in order to strenghten the understanding of that disaster management is one of main responsibilities of the government in providing protection to its people. It is also suggested that there be eight points/ areas of participation in managing disaster which are expected to provide cleaner patterns in local disaster management before, and after the disaster takes place.Key words : disaster threat, policy handling in regionsArtikel ini mencoba mengupas peran penting Pemerintah Daerah yang telah diberikan kewenangan oleh konstitusi dalam rangka penanganan bencana diwilayahnya. Penulis mendorong agar penanganan bencana dapat secara berkesinambungan dimasukkan ke dalam dokumen perencanaan pembangunan daerah, juga memberikan penguatan pemahaman bahwa penanganan bencana adalah salah satu tugas utama Pemerintah Daerah dalam rangka memberikan perlindungan kepada masyarakat. Diakhir tulisan, penulis merumuskan konsep delapan titik partisipasi penanganan bencana di daerah yang diharapkan dapat memberikan arah dan pola yang lebih jelas dalam penanganan bencana di daerah, pada saat dan setelah bencana terjadi.Kata kunci : ancaman bencana, kebijakan penanganan di daerah